Nintedanib‐αVβ3 Integrin Ligand Dual‐Targeting Conjugates towards Precision Treatment of Melanoma. Issue 45 (5th December 2022) - Bugatti, Kelly; Sartori, Andrea; Battistini, Lucia; Ruzzolini, Jessica; Nediani, Chiara; Curti, Claudio; Bianchini, Francesca; Zanardi, Franca
Abstract: Melanoma is the deadliest form of skin cancer, and more than 150, 000 cases are diagnosed every year in Europe. New strategies in treatment approved over the past decade, such as immunotherapy and targeted therapy, have prolonged life expectation even in stage IV melanoma patients. However, due to the increasing incidence of this cancer, the development of new therapeutic strategies remains urgent. Recent studies revealed the combination of nintedanib, a tyrosine kinase inhibitor approved as an antifibrotic drug, and immuno‐ and/or targeted therapy drugs to be promising. Here we present three new dual covalent conjugates, in which a nintedanib unit is permanently linked to a cyclopeptidomimetic ligand for the αV β3 integrin, a transmembrane receptor involved in cell survival, proliferation and migration, which is overexpressed by tumour cells, and therefore recognized as marker for tumour targeting. In vitro assays on human melanoma tumour cells confirmed the high binding affinity of these conjugates for αV β3 integrin‐positive melanoma cells, as well as their integrin‐mediated cell internalization. Two of these conjugates were efficient in inhibiting the mitogen activated protein kinase (MAPK) signalling pathway, common to both integrin‐ and growth factor‐ biological targets. Such targeted conjugates could therefore be of special interest in melanoma treatment alone or in combination with other anticancer drugs. Abstract : The synthesis and the in‐cell biological evaluation of three new drug‐integrin ligand covalent conjugates were performed to provide intelligent vectorization of the clinically approved drug nintedanib towards human melanoma cells, and to guarantee the biological action of the constituting units towards their respective receptor targets.